PENGARUH BIMBINGAN SOSIAL TERHADAP KENAKALAN REMAJA PADA PESERTA DIDIK SMP NEGERI 21 PONTIANAK - Hasanah, Nurul Wardatul; Asrori, Mohammad; Purwanti, Purwanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the influence of social guidance against juvenile delinquency in students class VIII SMP Negeri 21 Pontianak Year 2018. The method used is descriptive method in the form of correlational studies. The population in this study is all students of class VIII with the number of 278 students. Withdrawal samples that will be done by researchers using percentage of 20% of the total population of each class then the sample is 56 students. Data collection techniques used are indirect communication techniques and data collection tools in the form of questionnaires. Data analysis techniques using the formula percentage and poduct moment using SPSS version 16 then continued with the coefficient of determination. From the data analysis the researchers found that social guidance reached 96.85%, included in the high category. While juvenile delinquency reached 84.64% in high category. So the influence of social guidance on juvenile delinquency is 49.42%, meaning 51.58% juvenile delinquency is influenced by other variables not found in this study. Keywords: Social Guidance, Juvenile Delinquency